Epidemiologia da tuberculose em Sergipe: uma análise multifacetada - Lima, Shirley Verônica Melo Almeida (2020)
Tuberculosis is an infectious disease known worldwide for its vulnerability, magnitude and transcendence factors. It is considered a global health problem. Brazil has shown a steady decline in tuberculosis for a decade and a half, but it is still considered a country endemic to the disease. In Sergipe, the number of tuberculosis cases has increased. The objective was to analyze the epidemiological, spatial and temporal profile of morbidity and mortality from tuberculosis in Sergipe from 2001 to 2018. This is an epidemiological study of an ecological, temporal nature, with individual, collective and spatial approaches considering the Determinants Social Health. Databases of the information system for notifiable diseases and the mortality information system were used. Spatial and sociodemographic data were obtained by the Brazilian Institute of Geography and Statistics and the Institute for Applied Economic Research. Statistical analyzes comprised bivariate and multivariate logistic regression models, hierarchical regression models, trend and spatial analyzes and the making of a risk nomogram. The findings showed that there is an increasing trend in tuberculosis cases in children under 20 years old and between 20-39 years old, especially for males. The cure showed a decreasing trend. Abandonment of treatment represented 18.21% among those diagnosed with tuberculosis and the highest percentage of abandonment was in men (20%), race / black (20.3%), people between 20 - 39 years old (21 , 8%), with 4 to 7 years of study (23.6%), re-entry after previous abandonment (58.1%), with AIDS (42.3%), mental disorder (36.8%), alcohol use ( 31%), illicit drugs (39.3%), smoker (26.5%) and homeless population (55.4%). Predictive analysis showed that sociodemographic, behavioral and epidemiological characteristics are more likely to abandon treatment. Individuals living in municipalities with high HDI (OR: 1.91) and high-income inequality (OR: 1.81) are more likely to not complete treatment. Spatial dependence was observed regarding the incidence rate in almost all Sergipe territory. Spatial autocorrelation showed risk clusters in the Southeast and North of the state. Deaths due to tuberculosis showed a higher proportion among males, race / brown skin, the age group between forty and fifty-nine years and low education. Multivariate logistic regression identified the average incidence rate for tuberculosis (ORa: 1.06), the proportion of HIV tested (ORa: 7.10), people without primary education and informal occupation (ORa: 1.26) and people living in urban households without garbage collection (ORa: 0.10) as determinants associated with municipalities with higher TB mortality rates with ROC curve: 84% (p-value <0.001). It is concluded that access to health services, accelerated urbanization with large pockets of poverty and unhealthy housing conditions maintain the TB epidemic in Sergipe, corroborating global trends. Priority risk areas and groups were identified to support health planning, refine the focus of care and provide evidence regarding the spatial and temporal epidemiology of tuberculosis in Sergipe.